Building the Professional Firm: McKinsey & Co.: 1939-1968 - Bhide, Amar V. (Senate Hall, 2003)
Returns from investments made in a professional firm's capabilities and resources are not easily appropriable. Firm owners therefore tend to under invest in crucial intangible assets such as reputations and knowledge. This paper describes and analyzes how the founders of McKinsey & Co. overcame these problems to build one of the world's leading management consulting firms. McKinsey's success, I argue, derives from a system of professional norms, approach to serving clients, personnel policies, organization, governance and ownership which encourages firm members to identify with the long-term interests of the institution. Other firms cannot easily replicate this system because it incorporates difficult-to-codify trade-offs that have evolved through decades of trial and error and are now embedded in the firm's routines and tacit knowledge. The history and traditions of the firm have also inculcated values that encourage firm members to adhere to policies that they might, for short-term reasons, deviate from. The system's evolution is not however merely the result of a series of chance events. McKinsey's founders resorted to considerable trial and error, but it wasn't ad hoc; the experiments were intended to discover the best means to further a long-term vision and strategy. Moreover, their vision and strategy derived more from a priori faith and personal values than from scientific evidence or financial calculation.
Keywords: entrepreneurship|organizational development